Theoretical Foundations of Color Mass and Aesthetic Expression in Alisher Navoi’s Works - Qutliyeva Mahbuba Bekpulatovna (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This study examines the theoretical foundations of color mass and its role in aesthetic expression in the works of Alisher Navoi. It analyzes how color mass contributes to the creation of artistic imagery, emotional depth, and compositional harmony, highlighting its significance in both literary and visual art contexts. Navoi’s works demonstrate a deliberate use of color to enhance aesthetic perception, convey psychological states, and structure narrative imagery. The study also emphasizes the pedagogical value of understanding color mass for developing visual literacy and artistic competencies.